2020
DOI: 10.21037/atm-20-2200
|View full text |Cite
|
Sign up to set email alerts
|

Citri Reticulatae Pericarpium protects against isoproterenol-induced chronic heart failure via activation of PPARγ

Abstract: Background: Accumulated clinical trials and animal studies showed that Qiliqiangxin (QLQX), a traditional Chinese medicine formula containing extracts of 11 herbs, exerts beneficial effects on chronic heart failure (HF). Citri Reticulatae Pericarpium (CRP), one herbal medicine in QLQX, has been widely used in treatment against digestive, respiratory and cardiovascular diseases (CVDs) in China. However, the cardiac protective effects and mechanisms of CRP are still unclear.Methods: The effects of CRP were inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…It is characterized by impairment of cardiac systolic and diastolic functions, as well as irreversible cardiac dysfunction [1]. HF is a common end-phase of several cardiovascular diseases including hypertension, acute myocardial infarction, septic cardiomyopathy, and diabetic cardiomyopathy [2][3][4][5][6]. Alleviating cardiac dysfunction markedly prolongs the survival of patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by impairment of cardiac systolic and diastolic functions, as well as irreversible cardiac dysfunction [1]. HF is a common end-phase of several cardiovascular diseases including hypertension, acute myocardial infarction, septic cardiomyopathy, and diabetic cardiomyopathy [2][3][4][5][6]. Alleviating cardiac dysfunction markedly prolongs the survival of patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the effects of the traditional Chinese medicine qiliqiangxin capsule have revealed cardiac-protective functions mediated via PPAR γ regulation [ 8 ]. Citri reticulatae Pericarpium (CRP), a component of the qiliqiangxin capsule, inhibits pathological cardiac hypertrophy caused by multiple factors [ 9 , 10 ]. Nobiletin (NOB) is the active monomer isolated from CRP, with the molecular formula C 21 H 22 O 8 (the chemical structure is shown in Figure 1(a) ).…”
Section: Introductionmentioning
confidence: 99%
“…in the current study, to obtain more evidence to further transform the application of Sch a in clinical patient management, mice were used to construct cHF models for in vivo and nrVMs isolated from rat pups for in vitro. rat and mouse experiments are involved in the previous studies and, by contrast, the mouse cHF model is more mature, while the rat cell extraction is easier (30)(31)(32). The present study demonstrated the protective effects of Sch a in cHF via the administration of Sch a.…”
Section: Discussionmentioning
confidence: 99%